Multinuclear rhodium complexes supported by tetra-tert-butoxy disiloxide ligand: synthesis, structure, and reactivity. (3rd August 2022) - Ishizaka, Yusuke; Matsumoto, Kazuhiro; Sato, Kazuhiko; Choi, Jun-Chul
Abstract : The tetra- tert -butoxy disilicate ligand induced an unprecedented bis-dinuclear rhodium complex. Abstract : Rhodium siloxide complexes have been used as homogeneous catalysts and model compounds for silica-supported metal catalysts. However, rhodium complexes with multidentate siloxide ligands have rarely been prepared. In this study, a dinuclear rhodium complex supported by a bidentate tetra- tert -butoxy disiloxide ligand, Rh(COD)2 μ-(OSi(O t Bu)2 )2 O (3 ) (COD = cyclooctadiene), was synthesized and its basic reactivity was elucidated. When 3 reacted with carbon monoxide, a dinuclear rhodium carbonyl complex, Rh(CO)2 2 μ-(OSi(O t Bu)2 )2 O (A ), formed as an intermediate, which produced a bis-dinuclear rhodium carbonyl complex, [Rh(CO)2 2 μ-(OSi(O t Bu)2 )2 O]2 (4 ), by spontaneous dimerization. The dimerization of A could be attributed to the relatively weak electron-donating ability of the tetra- tert -butoxy disiloxide ligand, suggesting that substituents on siloxide ligands exert a significantly large effect on the formation of rhodium siloxide complexes. In addition, the reaction of 3 with trimethylphosphine (PMe3 ) afforded different dinuclear rhodium complexes, (PMe3 )Rh(COD)2 (OSi(O t Bu)2 )2 O (5 ), (PMe3 )2 RhRh(COD)μ-(OSi(O t Bu)2 )2 O (6 ), and Rh(PMe3 )2 2 μ-(OSi(O t Bu)2 )2 O (7 ), depending on the reaction temperature and the equivalent of PMe3 used, indicating that the substitution reaction of COD by PMe3 proceeds in a stepwise manner. Understanding the basic reactivity of these rhodium siloxide complexes may contribute to the development of silica-supported metal catalysts.